Astronomy’s Photographic Glass Plates: Demonstrating Value Through Use Cases - Kit Whitten; Lauren Boegen; Stephen Levine; Wayne Osborn; Elizabeth Griffin; Thurburn Barker; Jennifer Lynn Bartlett; Lindsay Smith Zrull; Daina Bouquin; Barbara Kern (Issues in Science and Technology Librarianship, 2024)
Astronomy's extensive collections of photographic glass plates contain historical images and spectra of celestial objects, documenting more than a century of the observable cosmos. Many reveal changes, both sudden (explosive), periodic, or gradual (evolutionary), which is material of immense interest for time-domain studies because of the long time-base they cover. Those early photographic observations also furnished all the basic data which supported our early understanding of the universe, and from which modern stellar classifications have been derived. Once the ubiquitous workhorse detector, plates or film are now replaced by electronic detectors, and systems are modified to take advantage of advances in telescope technology. This change poses challenges of preservation and accessibility for the plates, leading administrators to question the usefulness of the older materials in relation to the cost of their care and preservation. The following paper details many examples of reusing or re-purposing those plates, demonstrates their unique value to modern astronomy and the history of science, and makes a strong case for committing resources towards their long-term preservation and ultimately their comprehensive digitization.